EXAMINATION OF MJØSTÅRNET STRUCTURE IN THE CONTEXT OF WOODEN BUILDINGS AND SUSTAINABLE ARCHITECTURE RE-UTILIZATION OF NATURAL MATERIALS - Arici, Ayse (International Scientific Journal Vision, 2024)
This study examines the role of wood construction technologies in sustainable architecture and the reevaluation of natural materials, using the Mjøstårnet building in Brumunddal, Norway, as a case study. Mjøstårnet is notable as the tallest wooden structure in the world, serving as a pioneering example in the use of sustainability and environmentally friendly building materials. The article evaluates various aspects, such as the potential of wooden materials to reduce carbon footprints, energy efficiency, the building's innovative engineering solutions, and the durability of wood. Furthermore, it investigates how Mjøstårnet has transformed into a sustainable design model by integrating traditional and contemporary wood construction techniques, effectively using local resources and architectural aesthetics. This examination discusses how wooden structures present a sustainable alternative in the modern construction industry and explores the future potential of natural materials.